FRAGMENTS OF VENDIAN-EARLY CARBONIFEROUS OCEANIC CRUST OF THE PALEO-ASIAN OCEAN IN FOLDBELTS OF THE ALTAI-SAYAN REGION OF CENTRAL ASIA: GEOCHEMISTRY, BIOSTRATIGRAPHY AND STRUCTURAL SETTING - Safonova I.Yu.; Buslov M.M.; Kokh D.A.; Iwata K. (My University, 2004)
Detailed geological, geochemical and biostratigraphic studies of rocks from basaltic-sedimentary terranes in the Kurai and Katun accretionary wedges (Vendian-Middle Cambrian units), the Charysh-Terekta strike-slip zone (Late Cambrian-Early Ordovician units), and the Chara ophiolite-bearing strike-slip zone (Late Devonian-Early Carboniferous units) have been undertaken. The Early Cambrian accretionary wedges record a stage of the Kuznetsk-Altai island arc evolution. The Charysh-Terekta strike-slip zone records evidence of the Late Devonian collision of the Gondwana-derived Altai-Mongolian terrane and the Siberian continent. The Chara ophiolitic zone was formed during the Late Carboniferous-Permian collision of the Siberian and Kazakhstan continents.Our study of these fragments of oceanic crust led us to conclude that intra-plate volcanism was active at the early stages of the Paleo-Asian oceanic evolution, in a period from the Vendian to the Early Carboniferous. Fragments of weakly to strongly differentiated oceanic and island-arc basalts have been preserved in accretion-collision zones and give information about chemical composition, petrology and tectonic setting of the oceanic crust at these times. The geochemical data indicate that the Altai and East Kazakhstan metabasalts could have been formed at mid-oceanic ridges, oceanic islands or oceanic plateau of the Paleo-Asian Ocean. Our interpretation of structural, lithological, geochemical and biostratigraphic data shows that the structure and composition of the oceanic lithosphere of the Paleo-Asian Ocean were similar to those of the present Pacific Ocean.
Keywords: Vendian-Early Phanerozoic; Paleo-Asian Ocean basalts; geochemistry; biostratigraphy; Central Asia; Carboniferous; Vendian; Paleozoic::Carboniferous; Докембрий::Протерозой::Неопротерозойская::Вендский; Precambrian::Proterozoic::Neoproterozoic::Vendian; Палеозой::Каменноугольная